Mathematical foundations of complex networked information systems : Politecnico di Torino, Verrès, Italy 2009 /: Politecnico di Torino, Verrès, Italy 2009. ([2015]) - Kumar, P. R; Wainwright, Martin (Martin J.); Zecchina, Riccardo
No abstract available